PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PENGGUNAAN GAS ELPIJI TIGA KG DITINJAU DARI UU NO. 8 TAHUN 1999 (STUDI PADA MASYARAKAT KOTA MEDAN) - Ali Umar Harahap; Tan Kamello; Suhaidi Suhaidi; Hasim Purba (Universitas Sumatera Utara, 2016)
ABSTRACT Nowadays, people begin to shift from the use of kerosene to 3 kg elpiji (liquid natural gas) gas, and the government provides and distributes 3 kg elpiji to the people. In this case, the government is expected to maintain the quality of the product because it becomes the most important thing for consumers’ safety. If consumers’ right as stipulated in Law on Consumer Protection is not fulfilled, they have the right to file a complaint about the responsibility of PT. Pertamina for their loss in using 3 kg elpiji gas. The result of the research showed that why consumers’ right were not fulfilled was because of their lack of knowledge, education, and intensity and their indifference/apathy in using 3 kg elpiji gas, in handling its danger, and in consumer protection. This fact was supported by their lack of knowledge of how to handle its possible danger. They ignored the security in using 3 kg elpiji gas because they still used devices from conversion program. Article 19 of Law No 8/1999 on Consumer Protection states that business people are responsible for the compensation on damage, disgrace, and financial loss of consumers because of consuming produced or sold goods and services. The settlement of dispute between both parties is through the Court and settlement outside the Court is through BPSK (Consumer Dispute Settlement Board). Keywords: Consumer Protection, Dispute Settlement